Respostas
respondido por:
1
t (x) = y
para x = 0
(0 + 2) 2
4 = 4 = 16 (x= 0, y = 16)
x = - 1
- 1 + 2 1
4 = 4 = 4 (x = - 1, y = 4)
Aí vc monta o gráfico. x (horizontal) e y (vertical)
x = 1
1 + 2 3
4 = 4 = 4.4.4 = 64 (x = 1, y = 64)
para x = 0
(0 + 2) 2
4 = 4 = 16 (x= 0, y = 16)
x = - 1
- 1 + 2 1
4 = 4 = 4 (x = - 1, y = 4)
Aí vc monta o gráfico. x (horizontal) e y (vertical)
x = 1
1 + 2 3
4 = 4 = 4.4.4 = 64 (x = 1, y = 64)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás